Evaluación de los efectos de la variación de caudal sobre los niveles de amonio, nitrato y pH de un prototipo de cultivo acuapónico (2016)
This paper presents the results of the project “Design and implementation of an automated prototype for recirculation and filtration systems of water via the technique for detection of nitrate and ammonium combinations”, the prototype was built to scale in the laboratory, its general goal was to evaluate the effectiveness of the technique for detection of Nitrate and Ammonium combinations in the organic material of the system and its impact on the water quality, to this end we detected the level of Nitrate and Ammonium combinations present in the fish tank, we varied the water flow of the pump, allowing us to establish its relationship with the pH levels, temperature and ammonium and nitrate combinations in the fish tank, promoting operating conditions more appropriate to the process of filtering organic material and preserving the water quality of the system without needing to readjust it.